The limits of guilt - Loukas Balafoutas; Helena Fornwagner (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
According to the theory of guilt aversion, agents suffer a psychological cost whenever they fall short of other people's expectations. In this paper we suggest that there may be limits to this kind of motivation. We present evidence from an experimental dictator game showing that dictators display behavior consistent with guilt aversion for relatively low levels of recipient expectations, roughly up to the point where the recipient expects half of the available surplus. Beyond that point the relationship between expectations and transfers becomes negative. We argue that this non-monotonicity can help explain why the economic literature on guilt aversion offers conflicting findings on the relationship between expectations and behavior. Moreover, we examine this relationship at the individual level and establish a typology of subjects depending on how and whether they condition their behavior on recipient expectations. Our evidence is consistent with a simple theoretical model of guilt aversion.
Keywords: C91; D03; 330; guilt aversion; experiment; strategy method; greed